An Advanced Study on Ultraviolet Gain Characteristics of AlGaN/AlN in Nanotechnology - Lal, Pyare (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
This research work has been aimed to investigate an advanced study on Ultraviolet Gain Characteristics of advanced material AlGaN/AlN based hetero-nanostructure for various applications of purification and sterilization for today’s society in emerging technological nanophysics. In this research work, with the help of theory of effective masses of SM (Single and Multi) bands, the various appropriate UGPs (Ultraviolet Gain Parameters) have been computed simulatively. The behaviours of spectral performances of intensities of UV gain (in cm-1) with wavelengths (in nm) for AlGaN/AlN have been investigated by optimized techniques. This type of research work also provides the proper information about the modal confinement value of UV gain intensities (in cm-1) with several values of densities of carriers per unit volume (in cm-3) have been simulated and calculated systematically. In appropriate computational results, the crest value of UV gain intensities ( 1751 cm-1) has been achieved at the specific wavelength 254 nm. Hence, the utilities of this UV-light of wavelength 254 nm have played a substantial role in the purification and sterilization applications in today’s society. Moreover, the UV-lights of wavelength 254 nm have also extensively been used in better purification to disinfect the surfaces, air and water by eliminating the various types of viruses, bacterias and harmful contaminants.